PENINGKATAN PENGETAHUAN KECACINGAN PADA ORANG TUA SISWA SEBAGAI UPAYA PEMBERANTASAN KECACINGAN DI SDN MAMPANG 2 DEPOK - Harjono Hadiwiardjo, Yanti; Ima Maria; Pritha Maya Savitri; Dwi Arwandi Yogi Saputra (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
The most common group of children suffering from intestinal worms are primary school children. This condition is caused by children’s habit of not paying attention to hygiene, such as playing on the ground without paying attention to its cleanliness, not cutting nails, not washing hands with soap before and after eating, and not using footwear. Playing in an unclean environment and eating food carelessly can also be factors in the transmission of worms. Mothers’ knowledge as parents is essential in educating children to lead a clean and healthy lifestyle to prevent worm infections. This community service aims to increase parents’ knowledge about worms as part of efforts to eradicate this disease apart from deworming. This community service method was conducted at SDN Mampang 2 Depok by providing knowledge to 45 parents. The results of this service showed increased knowledge about worms among parents. Before the education, 20% of parents had poor knowledge, but after the education, all parents had good knowledge. This community service aims to increase parents’ knowledge about worms as part of efforts to eradicate this disease apart from deworming. This community service method was conducted at SDN Mampang 2 Depok by providing knowledge to 45 parents. The results of this service showed increased knowledge about worms among parents. Before education, 20% of parents had poor knowledge, but after education, all parents (100%) had good knowledge. The Wilcoxon test showed a significant difference in knowledge before and after education, with one subject experiencing a decrease in knowledge, 30 subjects experiencing an increase, and 14 subjects having a fixed knowledge. Therefore, interventions are needed in the form of education to parents and students to increase knowledge about clean and healthy living to avoid worms. — Kelompok anak yang paling banyak menderita cacingan adalah anak-anak Sekolah Dasar. Kondisi ini disebabkan oleh kebiasaan anak-anak yang kurang memperhatikan kebersihan, seperti bermain di tanah tanpa memperhatikan kebersihannya, tidak memotong kuku, dan tidak mencuci tangan dengan sabun sebelum dan sesudah makan, serta tidak menggunakan alas kaki. Bermain di lingkungan yang kurang bersih dan mengonsumsi makanan sembarangan juga dapat menjadi faktor penularan cacingan. Pengetahuan ibu sebagai orang tua sangat penting dalam mendidik anak-anak agar menjalani gaya hidup bersih dan sehat sebagai upaya pencegahan infeksi cacingan. Tujuan dari pengabdian kepada masyarakat ini adalah untuk meningkatkan pengetahuan orang tua siswa tentang cacingan sebagai bagian dari upaya pemberantasan penyakit ini selain dari pemberian obat cacing. Metode pengabdian ini dilakukan di SDN Mampang 2 Depok dengan memberikan pengetahuan kepada 45 orang tua siswa. Hasil dari pengabdian ini menunjukkan peningkatan pengetahuan tentang cacingan pada orang tua siswa. Sebelum diberikan edukasi, terdapat 20% orang tua yang memiliki pengetahuan yang kurang, namun setelah diberikan edukasi, seluruh orang tua (100%) memiliki pengetahuan yang baik. Uji Wilcoxon menunjukkan perbedaan pengetahuan yang signifikan sebelum dan sesudah pemberian edukasi, dengan 1 subjek mengalami penurunan pengetahuan, 30 subjek mengalami peningkatan, dan 14 subjek memiliki pengetahuan yang tetap. Oleh karena itu, diperlukan intervensi berupa edukasi kepada orang tua dan siswa untuk meningkatkan pengetahuan tentang hidup bersih dan sehat agar terhindar dari penyakit cacingan.